Ship Docking Motion Prediction and Collision-Risk Early Warning Using a Physics–SVR Model - Mingxin Li; Haolin Yang; Chao Ma; Yulei Zhu; Xide Cheng; Haoqin Huang (Journal of Marine Science and Engineering, 2026)
Reliable collision-risk warning during low-speed ship docking requires accurate and efficient hydrodynamic prediction. This study develops a physics-SVR (support vector regression) framework combining a three-degree-of-freedom maneuvering model with three SVR models that learn residuals in longitudinal force, lateral force, and yaw moment from computational fluid dynamics (CFD) data. The corrected loads support 120 s trajectory prediction and hull-envelope reconstruction. Minimum lateral and longitudinal clearances and their times to safety-threshold crossing distinguish normal, warning-alert, and emergency-alarm states. The database comprises 20 model-development conditions and three condition-level holdout tests representing unseen loading/draft, heading, and lateral-offset conditions. Across the holdout tests, overall relative errors decrease from 22.00–30.20% for the baseline model to 14.91–19.93%. In two hazardous cases, warning alerts precede contact by 154.9 and 172.09 s, while the non-hazardous control case triggers no alarm. The complete prediction-and-warning update requires 0.32 s on average, demonstrating potential for shore-based docking assistance under calm-water conditions.

Regulating ion mobility for intelligent “on-off” switchable electromagnetic wave absorption of ionogels in both GHz and THz band - Ruochu Lei; Zheng Cheng; Haolin Lu; Jianbin Wang; Zhiwen Zhou; Fei Fan; Bo Shan; Yi Huang (Chemical Engineering Journal, 2026)

Ecological characteristics and carrying capacity analysis of marine ranching ecosystem in Beibu Gulf based on Ecopath model - Cheng Cheng; Haolin Yu; Jie Feng; Yan Li; Qingxian Cao; Li Liu; Cheng Yang; Shan Zhao; Shuo Li; Zhen Zhang; Haiyan Wang; Tao Zhang (Journal of Oceanology and Limnology, 2026)

Programmed cell death in osteoarthritis - Haolin Li; Ping Chen; Weigang Cheng; Zhimin Zhang; Juanjuan Yang; Hao Zhang; Fangmei Jin; Lili Kan; Lei Chen; Haidong Wang (Apoptosis, 2026)

Local collaboration between oxygen vacancy, palladium and platinum trimer triggers exceptional performance in the alkaline fuel cell - Dinesh Bhalothia; Che Yan; Yawei Wu; Jui-Cheng Kao; Yu-Chieh Lo; Haolin Li; Nozomu Hiraoka; Hirofumi Ishii; Yen-Fa Liao; Sheng Dai; Chen-Hao Wang; Alice Hu; et al. (Chemical Engineering Journal, 2025)

Why hypochlorite in water cannot be detected by ion chromatography? - Yuheng Chen; Longjie Cheng; Pavel Nesterenko; Boqiang Li; Haolin Yang; Xiao Li; Lan Li; Baiyang Chen (Journal of Hazardous Materials, 2025)

Magnetic field oriented dual site S-Ni,FeOOH-M nanoarrays for enhanced oxygen evolution at high current densities - Jie Yu; Haolin Cheng; Yan Fu; Jinli Zhang (Chemical Engineering Journal, 2025)

Modulation of solvation chemistry and lithium deposition via magnesium bromide additives in lithium metal batteries - Jiayue Peng; Haolin Zhu; Jinghan Wang; Shijie Cheng; Jia Xie (Chemical Engineering Journal, 2025)

Rising frequency of ozone-favorable synoptic weather patterns contributes to 2015–2022 ozone increase in Guangzhou - Nanxi Liu; Guowen He; Haolin Wang; Cheng He; Haofan Wang; Chenxi Liu; Yiming Wang; Haichao Wang; Lei Li; Xiao Lu; Shaojia Fan (Journal of Environmental Sciences, 2025)

Identification of Key Genes Correlated with Economic Trait Superiorities and Their SNP Screening Through Transcriptome Comparisons, WGCNA and Pearson Correlation Coefficient in the Sea Cucumber Apostichopus Japonicus - Jingxian Sun; Haolin Wang; Yaoyao Zhan; Tanjun Zhao; Chengda Li; Cao Cheng; Zengdong Wang; Ange Zou; Yaqing Chang (Marine Biotechnology, 2025)

Rapid bromate determination using short-column ion chromatography-mass spectrometry: Application to bromate quantification during ozonation - Shi Cheng; Haolin Liu; Yanting Zuo; Feng Zhu; Huaicheng Zhang; Hao Zhang; Shouqiang Huang; Wentao Li; Zongli Huo; Aimin Li (Journal of Environmental Chemical Engineering, 2024)

Influence of boundary layer jets on the vertical distribution of ozone in Guangdong, China - Yuanping He; Shaojia Fan; Yiming Wang; Yiming Liu; Xiao Lu; Haolin Wang; Cheng He; Chuying Mai; Yu Du (Science of The Total Environment, 2024)

Integrated metabolome–metagenome analysis provides new insights into the impacts of sea cucumber (Apostichopus japonicus) aestivation on marine sediment composition - Wenhong Mai; Jingxian Sun; Haolin Wang; Chengda Li; Zengdong Wang; Cao Cheng; Ange Zou; Yaoyao Zhan; Yaqing Chang (Aquaculture, 2024)

Shale oil potential and mobility in low- to medium-maturity lacustrine shales: A case study of the Yanchang Formation shale in southeast Ordos Basin, China - Huairen Cao; Jun Shi; Zhao-Wen Zhan; Hao Wu; Xiaoyu Wang; Xin Cheng; Haolin Li; Yan-Rong Zou; Ping'an Peng (International Journal of Coal Geology, 2024)

Nitrogen-containing malodorous gas pollutants emission characteristics and health risk assessment from an A/O wastewater treatment plant - Yufan Dong; Linlin Ma; Yi Peng; Zhanhong Hu; Zongze Xu; Xiancong Jiang; Rong Cheng; Haolin Chen; Qing Yang (Journal of Water Process Engineering, 2023)

Insight into three water additives: Revealing the protective effects on survival and stress response under cold stress for Pacific white shrimp Litopenaeus vannamei - Lanfen Fan; Guowei Liao; Zhenlu Wang; Haolin Liu; Kaimin Cheng; Jun Hu; Yalin Yang; Zhigang Zhou (Fish & Shellfish Immunology, 2023)

Evolution of summer surface ozone pollution patterns in China during 2015–2020 - Youlang Zhang; Haichao Wang; Xiao Lu; Lei Li; Yuanping He; Haolin Wang; Guowen He; Cheng He; Jie Wang; Shaojia Fan (Atmospheric Research, 2023)

Decoding algae under abnormal temperature variability with odorant as a responsive indicator - Cheng Cen; Kejia Zhang; Tuqiao Zhang; Yingying Zheng; Peixuan Zhou; Haolin Lai (Science of The Total Environment, 2023)